2017
DOI: 10.1159/000458147
|View full text |Cite
|
Sign up to set email alerts
|

Single-Agent Pixantrone as a Bridge to Autologous Stem Cell Transplantation in a Patient with Refractory Diffuse Large B-Cell Lymphoma

Abstract: Aggressive non-Hodgkin lymphoma is associated with poor long-term survival after relapse or resistance to chemotherapy. We report a case of aggressive non-Hodgkin lymphoma refractory to first-line R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) and second-line R-DHAP (rituximab, dexamethasone, cytarabine, and cisplatin) chemotherapy treatments. The patient achieved remission with single-agent pixantrone, and received a consolidation with high-dose BEAM (BCNU, etoposide, cytarabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,462 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Three of the 10 responding patients in the PIXA registry subsequently received stem cell transplant after pixantrone. 18 Further studies evaluating the role of pixantrone in salvage regimens are of interest. The effectiveness of pixantrone in the current registry was also slightly better than in the aforementioned real-life retrospective study conducted in the UK, which reported median OS durations of 3.4 months, and an ORR of 24% (CR 10%; PR 14%), in a patient population similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the 10 responding patients in the PIXA registry subsequently received stem cell transplant after pixantrone. 18 Further studies evaluating the role of pixantrone in salvage regimens are of interest. The effectiveness of pixantrone in the current registry was also slightly better than in the aforementioned real-life retrospective study conducted in the UK, which reported median OS durations of 3.4 months, and an ORR of 24% (CR 10%; PR 14%), in a patient population similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This is a case report and to be honest with our readers, we must recognize that one swallow does not make a summer. This having been acknowledged, the report by Appio et al [2] raises a number of positive issues. The Pixantrone is a novel anthracenedione, and as such it is popularly referred to as an "anthracycline-like" drug.…”
mentioning
confidence: 99%
“…Many doctors actually do not know pixantrone, and if they do, they believe it is one more anthracycline. In this issue of the journal, Appio et al [2] report on a clinical case that clearly shows the might of pixantrone. They describe the case of a 56-year-old NHL patient who relapsed after R-CHOP, underwent second-line salvage therapy with rituximab, dexamethasone, high-dose cytarabine, and cisplatin (or oxaliplatin), but progressed before autologous stem cell transplantation could be performed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This report was also informative as alterations of coronary tone have long been known to occur for 5-fluorouracil and other fluoropyrimidines, while disturbances from tubulin-active agents were only partially known or suspected to occur. Appio et al [3] presented clinical insights from a patient treated with pixantrone for refractory/relapsed non-Hodgkin lymphoma. Their report focused primarily on pixantrone efficacy but, given the patient history (prior anthracycline treatment) and the structure of pixantrone (commonly but misleadingly described as an anthracycline-like drug), a major focus was also given to its cardiac safety.…”
mentioning
confidence: 99%